2019
DOI: 10.1007/s10552-019-01185-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment trends in head and neck cancer: Surveillance, Epidemiology, and End Results (SEER) Patterns of Care analysis

Abstract: Purpose-Recent advances in head and neck cancer (HNC) treatment, such as increased use of organ-preserving advanced radiation treatments, the approval of cetuximab for HNC treatment, and the increase in human papillomavirus (HPV)-related HNC, have changed clinical approaches to HNC management. We sought to identify treatment trends in a population-based cohort of HNC patients. Methods-The Surveillance, Epidemiology, and End Results Patterns of Care program collected additional treatment and HPV testing informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 46 publications
4
37
0
Order By: Relevance
“…In the United States, 2009 data from the Surveillance, Epidemiology, and End Results database showed that 82% of OC cancers, 28% of OP cancers, and 32% of L cancers were treated with primary surgery. 36 An analysis of National Cancer Data Base figures from 2004 to 2013 shows that for T1/T2 OP cancers, the rate of primary surgery rose from 56% in 2004 to 82% in 2013. 37 In Spain, data from Madrid illustrate that in 2017, 74% of OC cancers, 34% of OP cancers, and 71% of L cancers were treated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, 2009 data from the Surveillance, Epidemiology, and End Results database showed that 82% of OC cancers, 28% of OP cancers, and 32% of L cancers were treated with primary surgery. 36 An analysis of National Cancer Data Base figures from 2004 to 2013 shows that for T1/T2 OP cancers, the rate of primary surgery rose from 56% in 2004 to 82% in 2013. 37 In Spain, data from Madrid illustrate that in 2017, 74% of OC cancers, 34% of OP cancers, and 71% of L cancers were treated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer is the sixth most common cancer worldwide 1 . Radiotherapy with or without chemotherapy is an increasingly utilized potentially curative treatment that can afford organ preservation 2 . Radiotherapy causes repeated damage to effected tissue at the cellular and extracellular levels resulting in abnormal wound healing 3 …”
Section: Introductionmentioning
confidence: 99%
“…21,26 In our study we found that the incidence of HNSCC is more in age groups 41-50 years and >60 years as previously reported. 27 This finding suggests aging factor should be considered as risk factor for onset of HNSCC. One study reported that incidence of oral cancer has been increased while frequency of pharyngeal cancer has been reduced for the past few years in many populations worldwide.…”
Section: Discussionmentioning
confidence: 93%